Scale to Measure the Attitude of Farmers towards the Maize and Wheat Crops (Indian Journal of Extension Education, 2025)
Attitude plays a critical role in shaping one’s behavior towards any psychological object. Scales were created to examine farmers’ attitudes on maize and wheat crops. A list of 26 attitude statements for maize crop and 27 attitude statements for wheat crop was compiled and improved using Edward’s 14 principles, and included both positive and negative remarks. The study was conducted in 2024 with a total of 56 farmers in the sub-tropical zone, which included districts such as Akhnoor, Samba, and Kathua, and 56 farmers in the mid-hill zone, which included districts such as Rajouri, Kishtwar, Ramban, and Doda. Ultimately, each statement’s “t” value was calculated, and found that 13 statements for the maize crop and 11 statements for the wheat crop had a “t” value higher than 1.75, which were retained in order to assess the final scale’s validity and reliability. Cronbach’s alpha was proposed for assessing the reliability of attitude scales. In the case of scale for maize crop, the Cronbach’s alpha coefficient was 0.81, and 0.71 in the case of the wheat crop, validating the constructed scale’s internal consistency. The experts’ opinions were used to determine the scale’s content validity. With some changes, the ultimate scale will be used to gauge the attitude of farmers toward the maize and wheat crops.